Konsep Pembangunan Kota Inklusif Melalui Penataan Pedestrian di Kawasan Kota Lama Semarang - Ningrum, Aryani Praba (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
Semarang Old Town is a site that has a distinctive cultural image featuring classic-colonial architectural buildings which are an important historical part of the city of Semarang. The developments occurring in the Semarang Old Town area today, which has experienced an increase in its function as a tourist destination, are experiencing several new dynamic challenges and experiencing inequality, especially those related to mobility and accessibility, which are manifested in pedestrian arrangements. To reach several points in a comprehensive manner, the Semarang Old Town area must make itself an image of a walkable area for all groups. The Inclusive Town concept emphasizes the importance of integrating and taking into account community diversity in city planning and development. When this concept is applied to pedestrian planning in cultural heritage areas, the aim is to create a pedestrian environment that is accessible to all levels of society, including people who have special needs, as well as those from various cultural backgrounds. This research focuses on studying factors that must be taken into account, especially aspects of pedestrian planning that are friendly to all groups in cultural heritage areas. This research uses a literature review method related to inclusive cities relating to accessibility and pedestrians, as well as a comparative study of inclusive city planning which is considered successful in terms of pedestrian planning. This research produces several aspects that must be developed in governance to create an inclusive city, including universal accessibility, pedestrian safety, ease of access, sidewalk design, street furniture, and consideration of users with special needs. Through the realization of an inclusive city, it is hoped that the Semarang Old Town area will adapt and transform in providing cultural space for the community Kata Kunci:Semarang old town, cultural heritage, inclusive city, pedestrian Â